Integration schemes for hybrid and polygeneration concentrated solar power plants. Issue 6 (16th June 2021) - Cardemil, José M.; Starke, Allan R.; Zurita, Adriana; Mata‐Torres, Carlos; Escobar, Rodrigo
Abstract: Concentrated solar power (CSP) technologies have been developed over the past four decades for commercial operation, establishing them as reliable power generation sources in regions with high direct solar irradiance. The sizing of the solar field, thermal energy storage systems, and power block enables CSP plants to operate under various operating conditions, while also exhibiting capabilities to generate multiple products such as electricity, heat, desalination, and cooling. The limitations of CSP systems can be reduced by utilizing the positive traits of other technologies, thus resulting in hybrid plant configurations that can fully exploit different technology strengths while minimizing their individual weaknesses. This review presents the state of the art on CSP stand‐alone plants for both power generation and combined generation of different products. Subsequently, the characteristics of CSP plants hybridized with photovoltaics, wind, fossil fuels, and biomass systems are discussed for both power multiple‐product generation. The review of assessment methodologies provides suggestions for both assessment and performance analysis and comparison with other generation technologies. This review shows that hybrid CSP plants have clear advantages in terms of cost, flexibility of operation, adaptability, and capability for the multigeneration of different products compared with stand‐alone plants used to generate each product individually. Hybrid CSP plants have advantages and can be designed to satisfy multiple demands on a case‐by‐case basis and are valid alternatives to combinations of stand‐alone plants. This article is categorized under: Concentrating Solar Power > Systems and Infrastructure